2013
DOI: 10.1103/physrevd.88.014510
|View full text |Cite
|
Sign up to set email alerts
|

Hidden charm molecules in finite volume

Abstract: In the present paper we address the interaction of pairs of charmed mesons with hidden charm in a finite box. We use the interaction from a recent model based on heavy quark spin symmetry that predicts molecules of hidden charm in the infinite volume. The energy levels in the box are generated within this model, and from them some synthetic data are generated. These data are then employed to study the inverse problem of getting the energies of the bound states and phase shifts for DD or D * D * . Different str… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
56
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(62 citation statements)
references
References 81 publications
6
56
0
Order By: Relevance
“…The observed d * decay branchings into the diverse two-pion channels are consistent with expectations from isospin decomposition [28] as well as explicit theoretical calculations [29][30][31].…”
Section: Neutron-proton Induced Two-pion Productionsupporting
confidence: 73%
“…The observed d * decay branchings into the diverse two-pion channels are consistent with expectations from isospin decomposition [28] as well as explicit theoretical calculations [29][30][31].…”
Section: Neutron-proton Induced Two-pion Productionsupporting
confidence: 73%
“…It should be noted that although the bound state approaches its continuum limit as L increases, the potential approach has the advantage that it can connect the LQCD energy levels at moderate L or small L with the binding energies in the continuum in a quite accurate and model-independent way (for a relevant and extensive discussion, see, e.g., Ref. [62]). …”
Section: B the Inverse Problemmentioning
confidence: 99%
“…The lattice QCD simulation and related studies can be found in Refs. [649,650,651,652]. The analogous states of the X(3872), such as X b involving b quarks, were investigated in Refs.…”
Section: Lattice Qcdmentioning
confidence: 99%